Advances in clinical chemistry. - Makowski, Gregory S. (Gregory Stephen) (Academic Press is an imprint of Elsevier, 2019)
Advances in Clinical Chemistry, Volume 92 in this internationally acclaimed series, contains chapters authored by world-renowned clinical laboratory scientists, physicians and research scientists. The serial discusses the latest and most up-to-date technologies related to the field of clinical chemistry. It is the benchmark publication for novel analytical approaches in the clinical laboratory. Key Features: Provides the most up-to-date technologies in clinical chemistry and clinical laboratory science; Authored by world renowned clinical laboratory scientists, physicians and research scientists; Presents the international benchmark for novel analytical approaches in the clinical laboratory. Readership: Clinical Laboratory Professionals, Physicians and Research Scientists.